Radiographic lumbosacral angle has a low yield for diagnosing low back pain in workers 20-70 years of age - Partogi Napitupulu; Gupita Nareswari; Mulia Rahmansyah; Tandy Chintya Tanaji (Faculty of Medicine, Universitas Trisakti, 2022)
BACKGROUNDThe increasing trend of working from home (WFH) among workers may lead to prolonged sitting time, which is associated with increased complaints of low back pain (LBP). The lumbosacral angle (LSA) is one of the clinically important radiographic angles related to the curves commonly measured to evaluate the biomechanical factors linked with LBP. The purpose of this study was to determine the yield of radiographic LSA for diagnosing LBP among workers aged 20-70 years. METHODS An analytic cross-sectional study involving 119 participants was carried out in Trisakti University. Lumbosacral angle was measured using Ferguson’s method. Data regarding LBP symptoms, sitting duration, and sitting position were collected using a questionnaire. Sensitivity and specificity was used to describe the characteristics of LSA as a screening test of LBP. RESULTSThe subjects consisted of 66 women (55.5%) and 53 men (44.5 %). Their ages ranged from 20 to 64 years with a median age of 40.0 years. Mean LSA was 37.4 ± 7.3º, while the prevalence of LBP was 75 (63.0%). The optimal cut-off value of LSA for the prediction of LBP was 49.5% (95% CI: 0.385-0.606). The sensitivity, specificity, positive predictive value and negative predictive value of LSA in detecting LBP were 58.7%, 45.5%, 68.8%, and 43.6%. CONCLUSIONSThe radiographic lumbosacral angle has a low yield for the diagnosis of LBP among workers aged 20-70 years. Further studies are needed to confirm our results and to test the application of this measurement.